Pawsitive Care: Canine-Assisted Intervention for Anxiety in ICU Patients and Family Members: A Single-Center, Single-Arm Study - Kathleen Cook, DipCritCare; Clare Robertson, DipCritCare; Kiran Gudivada, DM; Imogen Mitchell, PhD; Mary Nourse, GradCertIntCareN; Megan M. Hosey, PhD; Catherine Paterson, PhD; Sumeet Rai, FCICM (Critical Care Explorations)
OBJECTIVES:. To investigate the effect of canine-assisted intervention (CAI) on anxiety symptoms among intensive care patients and their family members. DESIGN:. Prospective, single-center, single-arm, nonrandomized, within-subject study design. SETTING:. Tertiary hospital ICU. PATIENTS/SUBJECTS:. Adult (≥ 16 yr) ICU patients and their family members. INTERVENTIONS:. Individual CAI (therapy dog) sessions, lasting at least 15 minutes. MEASUREMENTS AND MAIN RESULTS:. Primary outcome: change in Visual Analog Scale for Anxiety (VAS-A) among patients and family members; secondary outcomes (patient cohort): change in: 1) Numeric Pain Rating Scale, 2) physiologic vital signs, and 3) intervention-related adverse events. A total of 141 participants (70 patients and 71 family members) were recruited. The median (interquartile range [IQR]) age (yr) was 63 (49–71) for patients, and 51 (36–61) for family members. There was a significant reduction in anxiety scores after the intervention, with median (IQR) VAS-A scores changing from 5 (1–7) to 0 (0–4 [p < 0.001]) for the patient cohort and from 6 (5–8) to 3 (1–5 [p < 0.001]) for the family cohort. Majority of patients (56/70 [62%]) and family members (63/68 [93%]) demonstrated a greater than or equal to 2-point reduction in VAS-A scores. In terms of pain, median (IQR) scores among the patient cohort were also lower post-intervention (0 [0–5] vs. 0 [0–2]; p < 0.001). There were no statistically significant changes in physiologic vital signs (heart rate, respiratory rate, and systolic blood pressure) among patients following the intervention. Additionally, there were no reported dog bites, scratches, or other adverse events during CAI. CONCLUSIONS:. CAI offers immediate therapeutic benefits in reducing anxiety symptoms in ICU patients and their family members with no observed adverse effects. It may also have a potential role as an adjunctive therapy for pain management in ICU patients. Further research should explore the influence on longer-term psychologic outcomes for ICU patients and family members.